2008
DOI: 10.28945/442
|View full text |Cite
|
Sign up to set email alerts
|

The Changing Face of Information Systems Research:A Longitudinal Study of Author Influence

Abstract: This paper examines the impact of key authors on Information Systems research from 1986 to 2005 and analyzes changes in influence and research interests over this period. The author set was based on publication counts in top Information Systems journals, supplemented on a reputational basis with authors recognized for their contribution to the field. Citation analysis was used to identify the most influential authors and to examine changes in influence across four five-year time periods. The results show that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Bibliometric approaches that purport to be indicators of research quality have their origins with Garfield's (1972) work on citations, and their most recent expression in the changes proposed for the United Kingdom's research assessment exercise (Adams 2008). Countering an earlier finding by Doyle and Arthurs (2000), Taylor and Dillon (2007) found that highly cited articles are generally those published in more highly ranked journals. Thus, the proportion of an individual researcher's or a business school's published papers that are in journals of higher rank, might be considered to be a measure of research quality.…”
Section: Introductionmentioning
confidence: 67%
“…Bibliometric approaches that purport to be indicators of research quality have their origins with Garfield's (1972) work on citations, and their most recent expression in the changes proposed for the United Kingdom's research assessment exercise (Adams 2008). Countering an earlier finding by Doyle and Arthurs (2000), Taylor and Dillon (2007) found that highly cited articles are generally those published in more highly ranked journals. Thus, the proportion of an individual researcher's or a business school's published papers that are in journals of higher rank, might be considered to be a measure of research quality.…”
Section: Introductionmentioning
confidence: 67%
“…According to the results of co-citation and citation burst analysis, the most basic and classical theme in the IS domain is 'IT use and acceptance', which has been discussed in various contexts, such as the organization, online shopping, social media. In fact, information systems is an emerging applied subject, originating from the background of organizational management (Taylor et al, 2008) (Taylor et al, 2008)[44] . Initially, information systems aims to study the traditional issues related to information technology use in the organization context, such as 'information technology acceptance in organization' and 'organization knowledge management systems'.…”
Section: Future Research In the Is Fieldmentioning
confidence: 99%